Sensitive Sectors in Free Trade Agreements - Alan V. Deardorff (East Asian Economic Review (EAER), 2018)
This paper documents the presence of "sensitive sectors" in Free Trade Agreements, defined as sectors for which the within-FTA tariffs remain positive. The paper includes some brief theoretical discussion of the welfare implications of these, but the main emphasis is on reporting two measures of this phenomenon for countries in FTAs that entered into force between 1994 and 2003. One measure is the percentage of tariff lines that remain dutiable, and the second is the change, from before the FTA to after, in the average maximum (across 6-digit products) positive tariffs. Both measures are derived from data in the UNCTAD TRAINS database, and are then related to measures of country characteristics that might explain them. Low per capita GDP countries tend to have larger fractions of dutiable tariff lines, while higher income countries tend to post larger increases in average maximum positive tariffs. Both suggest that the favored treatment of sensitive sectors is undermining the potential gains from trade that FTAs could provide.
Keywords: F10; F13; F15; 330; Free Trade Agreements; Sensitive Sectors; Exempted Sectors; Trade Diversion; Tariff Lines